From Conflict to Cooperation: A Macromarketing View of Sustainable and Inclusive Development in Lebanon and the Middle East - DeQuero-Navarro, Beatriz; Aoun Barakat, Karine; Shultz, Clifford J.; Araque-Padilla, Rafael A.; Montero-Simo, Maria Jose (Environmental management (New York), 2020)
Since the beginning of the Syrian war, Lebanon has experienced a major population change and has become the country with the highest number of refugees per capita. The authors apply a macromarketing perspective to study the effects of this population growth on the environmental management of Lebanon, with implications for the Levant and broader Middle East. An analysis of several factors, including geography, climate, population, economics, and politics, offers a holistic and integrative assessment of resource management, quality-of-life (QOL), economic diversification, and inclusive employment. Attention is given to social dilemmas in Lebanon’s consociational politics, and how these dilemmas may be affecting policy making and ultimately sustainable development—locally, nationally, and regionally. The authors share a systemic framework to facilitate understanding and solutions via cooperation and constructive engagement of catalytic institutions, consideration for all stakeholders, and innovative projects that include refugees for best practices to promote sustainable and equitable development, and ultimately peace and prosperity in Lebanon and the Middle East.